Lepidoptera of South Ossetia (Northern Transcaucasia). Part III. Tortricidae, Pterophoridae and Alucitidae (Insecta: Lepidoptera) - Nedoshivina, Svetlana V.; Ustjuzhanin, Peter Ya; Kovtunovich, Vasiliy N.; Streltzov, Alexander N.; Yakovlev, Roman V. (SHILAP Revista de lepidopterologia)
In the third part of the publication, we present the faunal list of four families of the Microlepidoptera of South Ossetia, including 64 species of Tortricidae, 17 species of Pterophoridae and 5 species of Alucitidae. All species are reported for South Ossetia for the first time. Phtheochroa purana (Guenée, 1845), Gynnidomorpha minimana (Caradja, 1916), Eupoecilia sanguisorbana (Herrich-Schäffer, 1856), Cochylis pallidana Zeller, 1847, Ancylis unguicella (Linnaeus, 1758), A. paludana (Barrett, 1871) (Tortricidae), and Capperia salanga Arenberger, 1995 (Pterophoridae) are found in the Caucasus for the first time. Stenoptilia arida (Zeller, 1847), Stangeia siceliota (Zeller, 1847) (Pterophoridae), and Alucita ordubadi Zagulajev, 2000 (Alucitidae) are found in the Greater Caucasus for the first time.